The potential and promotion of entotourism in Gunung Ledang, Johor, Malaysia - Maricel, Cuevas David (2015)
This research tries to provide the scientific evidence that insect tourism or entotourism has potential and is viable. This is achieved through two methods – field observation and data collection, and through questionnaire surveys on tourist perceptions on insects and entotourism. Gunung Ledang was chosen as the research site for several reasons including the easy access to tourist respondents. Surveys showed that tourists are interested in insect. Supported by field observations and data collection, insects have potential to be excellent nature tourism product. Closer examination pointed out that insect groups that are reliable and visible are ants, butterflies, termites, dragonflies, moths, beetles, cicadas and damselflies. Field trials indicated that these insects were viable attractions as they are readily visible, safe, easily recognizable, with some having linkage to local culture. Regardless of the different environmental ambience, time of observation (except early mornings) and seasons, insect were always present. The tendency is there however, that particular environment such as water body (pool/waterfall) would attract certain insects such as odonates. Further surveys on tourists’ perception indicated that they supported entotourism and were willing to participate in one. As Gunung Ledang is a national and state park under the jurisdiction of the Perbadanan Taman Negara Johor (PTNJ), their staff would likely be the candidates as entotourism operators. Thus, this research also gauged the present level of understanding and knowledge on insects by PTNJ staff, supplemented by a training course. Statistically, there is significant increase in the understanding and knowledge of insects after the training. A small booklet was developed based on collections of insects from Gunung Ledang and used during the training. Although, much of the research is about evaluating the potential and viability of insects as tourism product, to diversify tourism products, in line with the Malaysia Government’s agenda, it also pointed out the need to conserve Gunung Ledang (watershed with high ecological values and with cultural heritage).